The Canadian collaborative project on genetic susceptibility to multiple sclerosis cohort population structure and disease etiology - Pagalilauan, Alison M.; Everest, Elif; Rachimi, Suzanna; Reich, Daniel S.; Waldman, Alex D.; Sadovnick, A. Dessa; Vilarino-Guell, Carles; Lenardo, Michael J. (Frontiers in Neurology, 2025)
BackgroundPrevious genetic and epidemiological studies have examined subpopulations from the Canadian Collaborative Project on Genetic Susceptibility to Multiple Sclerosis (CCPGSMS) patient cohort, but an encompassing analysis of the study population has not yet been carried out.ObjectiveThis retrospective study examines patterns of multiple sclerosis (MS) prevalence in 13,663 cohort members, including 4,821 persons with MS or suspected MS and 8,842 family members.MethodsWe grouped participants into epidemiologic subgroups based on age of MS onset, clinical stage at diagnosis, symptom type at disease onset, sex, proband status, disability as measured by the EDSS, and ancestry based on reported ethnicity.ResultsWe observed a 2.7:1 MS prevalence ratio of women to men, though disease severity was greater for male patients. Variation in the age of disease onset between patients was only slightly associated with sex and strongly associated with disease type. Specific types of clinical symptoms at disease onset were associated with the prognosis. Regional residence did not correlate with disease onset, type, or severity.ConclusionPopulation trends, as presented here, are not explained by environmental factors alone, highlighting the need for a comprehensive genetic analysis to understand disease variance across families.